2005
DOI: 10.1016/j.vetpar.2004.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the repeated distribution of sainfoin hay on the resistance and the resilience of goats naturally infected with gastrointestinal nematodes

Abstract: Due to the high prevalence of anthelmintic resistance in goats, the need to explore novel approaches to control nematodes and to reduce the exclusive reliance on chemotherapy is strongly demanded in this host species. In sheep, several studies have shown that the consumption of tannin-rich legume forages was associated with positive effects on host resilience and resistance to parasite infection. In goats, studies on such interactions between tanniferous plants and nematode infections remain few. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 25 publications
9
62
1
2
Order By: Relevance
“…The supplementation with tannin-containing heather significantly reduced the goat mortality rate, which is consistent with previous studies reporting the positive effect of tannin consumption on the resilience of goats (Paolini et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The supplementation with tannin-containing heather significantly reduced the goat mortality rate, which is consistent with previous studies reporting the positive effect of tannin consumption on the resilience of goats (Paolini et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…This could reduce dependence on conventional chemotherapy, to which many parasite species have developed resistance, and facilitate the sustainable control of GI nematode parasitism (Githiori et al, 2006;Hoste et al, 2006). Parasite-infected goats that consume moderate quantities of tannin-containing plants show improved resistance and resilience to parasites, and significant decreases in faecal egg counts (FEC) and parasite burden (Min et al, 2005;Paolini et al, 2005;Osoro et al, 2007a and2007b). Goats can, however, also experience the anti-nutritional effects of tannins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, a reduction of this magnitude may downsize infection risk for parasite naïve animals grazing the pasture subsequently. Our results are in line with the findings of other studies which found a FEC reduction of comparable size in lambs (Heckendorn et al, 2007) and goats (Paolini et al, 2005). The administration of faba bean did not have an effect on egg excretion.…”
Section: Discussionsupporting
confidence: 93%
“…In Central Europe (e.g. France, Switzerland) studies have focused on the anthelmintic effect of the tannin containing legume sainfoin (Onobrychis viciifolia) of the fabaceae family (Heckendorn et al, 2007;Heckendorn et al, 2006;Paolini et al, 2005). The choice of this species is mainly linked to its comparatively good agronomic properties under Central European climate conditions (Häring et al, 2007), amongst which the tolerance of O. viciifolia to cold, drought and low nutrient status are of particular importance (Carbonero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In regards to the use of tanniferous plants and condensed tannins to control GINs, a variety of tanniferous plants and tannin extracts have been tested such as Acacia karoo and A. nilotica (Kahiya et al, 2003), big trefoil (Lotus pedunculatus) and birdsfoot trefoil (Lotus corniculatus) (Marley et al, 2003;Heckendorn et al, 2007), cassava forage (Sokerya and Preston 2003), sainfoin (Onobrychis viciifolia) (Paolini et al, 2003b;Hoste et al, 2005a;Paolini et al, 2005;Heckendorn et al, 2006;Manolaraki et al, 2010), Sericea lespedeza (Min et al, 2004;Shaik et al, 2004;Min et al, 2005;Shaik et al, 2006;Terrill et al, 2007;Moore et al, 2008), sulla (Hedysarum coronarium) (Niezen et al, 2002;Pomroy and Adlington 2006), heather (Osoro et al, 2007;Frutos et al, 2008;Osoro et al, 2009), Lysiloma latisiliquum (Brunet et al, 2008;Martínez-Ortíz-de-Montellano et al, 2010), Lespedeza cuneata (Lange et al, 2006;Terrill et al, 2009), quebracho extract (Paolini et al, 2003a;Paolini et al, 2003c), condensed tannin cracked grain sorghum (Whitley et al, 2009), and wattle tannin (Max et al, 2009;Max 2010) with experimentally GIN infected or naturally infected goats. It is obviously from these studies that tannins could have detrimental effects on development into L3 larvae, establishment of GIN infective larvae, worm fecundity, and worm burden in goats.…”
Section: Effect Of Tanninsmentioning
confidence: 99%